The wretched [videorecording (DVD)] - Pierce, Brett; Pierce, Drew; Howard, John-Paul; Curda, Piper; Jones, Jamison; Tesfai, Azie (IFC Films, 2020)
Following his parents' separation, a rebellious teenage boy is sent to live with his father for the summer and work at the local marina to gain some form of discipline. The idyllic tourist town offers little solace for him, however, and Ben's problems grow increasingly disturbing when he makes a chilling discovery about the family renting the house next door.